Are the passengers of transatlantic flights and health service staff familiar with the economy class syndrome and antithrombotic prophylaxis? - Gattermayer, Bożena; Spannbauer, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2013)
Introduction : One of the urgent issues of transport medicine is the so-called “economy class syndrome” manifested by deep vein thrombosis (DVT) of the lower limbs. The risk of venous thromboembolism after long-haul aeroplane flights is not low and it is probably related to the specific aircraft cabin environment, individual predispositions, prolonged sitting in the “coach” position and poor awareness of this issue. Aim study : The objective of this study was to assess the awareness of DVT linked to the long-haul flight, both of passengers of transcontinental flights and of health service representatives. The extent of widely understood antithrombotic prevention among passengers was also analysed. Additionally, we intended to propagate the problem of the economy class syndrome. Material and methods : Two independent groups were included in the study. The first one was composed of 50 passengers (19 males and 31 females) awaiting a flight to Chicago. The other was made up of health service representatives, i.e. 150 nurses – from a variety of clinical specialties, and 19 general family doctors. Results : 84% of passengers have never heard of the flight-associated thrombosis. None of the examined passengers has received any information about this problem either from the airline staff or from health service staff. Just 10% out of all examined passengers have used the antithrombotic prophylaxis. In the group of health service staff, as many as 95% of nurses and 79% of physicians did not know what the term “economy class syndrome” meant. Only 1% of nurses have made their patients familiar with this issue. None of the asked physicians has ever discussed the risk of DVT linked to long-haul flights with their patients. Conclusions : The awareness of the economy class syndrome among passengers and representatives of medical personnel is still very low. Knowledge of the venous thrombosis risk factors and the antithrombotic prophylaxis among travellers is insufficient. Both airlines and medical staff do not properly inform travellers on the potential risk of the economy class syndrome.